Horticultural Supply Chain Models: Strategies, Challenges, and Marketing Approaches. - Azmi, Azmi; Hadiguna, Rika Ampuh; Jonrinaldi, Jonrinaldi (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2025)
Indonesia's horticulture sector has undergone rapid expansion, driven by rising demand from both domestic and international markets. However, small-scale farmers continue to struggle with limited market access, price volatility, and high production costs, affecting their profitability and long-term sustainability. This study conducted a comprehensive literature review of 135 scientific articles to analyze three dominant supply chain models: direct marketing, contract farming, and cooperatives. Direct marketing allows farmers to secure higher prices by bypassing intermediaries but poses challenges in terms of operational scale, financial resources, and market access. Contract farming provides stability through guaranteed pricing, input support, and technical assistance, though profit distribution often favors contracting firms. Meanwhile, cooperatives offer better market access and collective bargaining power but require strong organizational structures to function effectively. The findings emphasize the importance of policies that support farmer education, improve market infrastructure, and encourage fair contractual agreements. Additionally, agribusiness stakeholders must invest in supply chain innovations and risk mitigation strategies to enhance efficiency and transparency. Strengthening these aspects is crucial for fostering a more resilient and sustainable horticultural sector in Indonesia